Diagnostic value of culture and serological tests in the diagnosis of histoplasmosis in HIV and non-HIV Colombian patients (2013)
ABSTRACT : We determined the value of culture and serological tests used to diagnose histoplasmosis. The medical records of 391 histoplasmosis patients were analyzed. Diagnosis of the mycosis was assessed by culture, complement fixation, and immunodiffusion tests; 310 patients (79.5%) were male, and 184 patients (47.1%) were infected with human immunodeficiency virus (HIV). Positivity value for cultures was 35.7% (74/207), reactivity of serological tests was 95.2% (160/168), and a combination of both methodologies was 16.9% (35/207) for non-HIV patients. Positivity value for cultures was 75.0% (138/184), reactivity of serological tests was 92.4% (85/92), and a combination of both methodologies was 26.0% (48/184) for HIV/acquired immunodeficiency syndrome (AIDS) patients; 48.1% (102/212) of extrapulmonary samples from HIV/AIDS patients yielded positive cultures compared with 23.1% (49/212) in nonHIV patients. Lymphocyte counts made for 33.1% (61/184) of HIV/AIDS patients showed a trend to low CD4+ numbers and higher proportion of positive cultures. These results indicate that culture is the most reliable fungal diagnostic method for HIV/AIDS patients, and contrary to what is generally believed, serological assays are useful for diagnosing histoplasmosis in these patients.